2013
DOI: 10.1371/journal.pone.0061925
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nuclear Factor-Kappa B Activation Decreases Survival of Mycobacterium tuberculosis in Human Macrophages

Abstract: Nuclear factor-kappa B (NFκB) is a ubiquitous transcription factor that mediates pro-inflammatory responses required for host control of many microbial pathogens; on the other hand, NFκB has been implicated in the pathogenesis of other inflammatory and infectious diseases. Mice with genetic disruption of the p50 subunit of NFκB are more likely to succumb to Mycobacterium tuberculosis (MTB). However, the role of NFκB in host defense in humans is not fully understood. We sought to examine the role of NFκB activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 72 publications
6
93
0
Order By: Relevance
“…Furthermore, AM incubated with AIM showed a significant increase in Bcl-xL expression, a pro-survival, anti-apoptotic molecule. We have found that NFkB e well known to be activated by both CS and exogenous ROS e is a potent inhibitor of apoptosis and autophagy in human macrophages, ultimately impairing control of MTB [13]. This finding is corroborated by studies showing that nicotine inhibits apoptosis [28].…”
Section: Cs Likely Does Not Affect Phagocytosis Of Mtb But Inhibits Esupporting
confidence: 57%
See 1 more Smart Citation
“…Furthermore, AM incubated with AIM showed a significant increase in Bcl-xL expression, a pro-survival, anti-apoptotic molecule. We have found that NFkB e well known to be activated by both CS and exogenous ROS e is a potent inhibitor of apoptosis and autophagy in human macrophages, ultimately impairing control of MTB [13]. This finding is corroborated by studies showing that nicotine inhibits apoptosis [28].…”
Section: Cs Likely Does Not Affect Phagocytosis Of Mtb But Inhibits Esupporting
confidence: 57%
“…AM can be classified into two main subtypes: (i) the classically-activated M1 phenotype, characterized by production of pro-inflammatory cytokines and IFNg-inducible gene expression and (ii) the alternatively-activated M2 or "deactivated" phenotype, characterized by increased activity of arginase, matrix metalloproteinase (MMP), transforming growth factor-beta (TGFb), IL-10, and prostaglandin E 2 [11,12]. M1 macrophages orchestrate host protective responses against MTB by producing cytokines, chemokines, and adhesion molecules that recruit and activate other immune cells but also directly kill MTB by phagosome-lysosome (P-L) fusion, autophagy, and apoptosis or at least help contain the infection by participating in the formation of well-formed granulomas [13,14]. M1 macrophages also process mycobacterial antigens and activate IFNg-producing CD4 þ and CD8 þ T cells that are vital for controlling MTB infection.…”
Section: Murine Studies On Cs and Susceptibility To Tbmentioning
confidence: 99%
“…We found that granulomas in the containment set have shorter NF-B signal activation intervals than those granulomas in the disseminating set. Recently, Bai et al published work suggesting that inhibition of NF-B activation (i.e., shorter signal activation intervals) decreases survival of M. tuberculosis in human macrophages (112). They used an inhibitor of IBa kinase to inhibit NF-B activation and found a significant decrease in the number of viable intracellular mycobacteria recovered from THP-1 macrophages at both 4 and 8 days after infection.…”
Section: Discussionmentioning
confidence: 99%
“…NF-B inhibition induces autophagy by increasing the formation of autophagosomes (106), and MAPK triggers the expression of NF-B (107,108). This suggests that MsmRv3242c infection activates the MAPK pathway, which subsequently activates p-NF-B and IL-10, resulting in inhibition of autophagy.…”
Section: Discussionmentioning
confidence: 99%